Ten notes on the social and educational pact - Tedesco, Juan Carlos (Avances en Supervisión Educativa, 2010)
Alter specifying the meaning of compromise, the author analyses some of its requirements and features. A compromise must be a part in a general social process standing upon the construction of a fair society, one that obliges every social segment to discuss its opinion and to negotiate publicly. It warns about the need of planning carefully these agreements and it also suggests that the parts in charge of coming to an agreement often do not know what exactly will be the consequences of those terms, since only in the implementation phase of the process the real size of the previously designed strategies will eventually turn up.